IMPLICATION CBI TOWARDS ADULT LEARNERS’ BUSINESS ENGLISH CORRESPONDENCE SKILLS - Wardana I Ketut; Astawa I Nengah (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Mahasaraswati Denpasar, 2021)
Analysing the ability of the employees in business English correspondence seems challenging in edult learners teaching because it can encourage the psycholingusitic domain in bilingual learning. The present study attempted to find out whether the writing skill of the employees in Sukavathi villa in business English correspondences skills can be improved through content based instruction (CBI). The subject of the present study was 32 employees. The main characteristic of the study was an action reaseach with descriptive approach. Moreover, series of test and observation techniques were used to collect the data that were anaylised descriptively. The result revealed that the CBI impacted the students’ abilities in writing English formal and informal letters or E-mails for any business purposes. The mean score of the pre-test was 54.56 that is categorized poor. After the implementation of CBI, the achievement increased from 63.81 to 80.25, being categorized very good. Furthermore, the learning process with CBI showed that 10% of employee incolved low participation, 25% moderate partcipation, and 65% high participation. The study suggest that bililngual learning for adult learners requires affective encouragement, commitment, and stimulation towards the target language mastery